Determinism and reactive attitudes: reflections on our alleged unrenounceable commitments - Kelland, Lindsay-Ann (Rhodes University, Faculty of Humanities, Department of Philosophy, 2009)
There seems to exist a tension between our metaphysical and phenomenological commitments in the free will debate. On the one hand, I argue that at the metaphysical level we cannot coherently defend the belief that we are morally responsible in the sense that we deserve to be rewarded and punished for our actions, where desert-entailing moral responsibility is the primary understanding of moral responsibility presupposed in the free will debate. I argue that we are responsible for our actions but only in the weaker sense, termed 'attributability' by Gary Watson. On the other hand, we are allegedly unrenounceably committed at the phenomenological level to conceiving of, and treating, ourselves and one another as morally responsible beings in the desert-entailing sense. P. F. Strawson famously defends this claim in his seminal work, 'Freedom and Resentment'. In my thesis I will set out this tension by exploring both commitments in turn. I then aim to show that the tension can be dissolved by arguing, contra P. F. Strawson, that our phenomenological commitment is not in fact unrenounceable. The dissolution of this tension entails, I argue, that we must examine our conception of self and other. We must explore the implications of adopting a position which denies that we are morally responsible beings for our life-hopes, personal feelings, inter-personal relationships and projects. Most importantly, I argue that we must renounce our current retributive condemnatory practices which are based on the unjustified belief that we are morally responsible beings.
Keywords: Free will and determinism; Responsibility